(untitled) (Far Eastern Federal University: School of Engineering Bulletin, 2022)
High-strength building ceramics are characterized by increased shard density, compressive strength and frost resistance, which affect the durability of products. Materials with such properties are porcelain stoneware and clinker bricks. Based on the analysis of the phase composition of these materials, an attempt to predict rational temperature regimes and formulations that ensure the achievement of such properties in building ceramics has been made. The analysis of the phase composition showed the presence of both amorphous and crystalline phases in the compared samples, represented by β-quartz, mullite, β-cristobalite, leucite and hematite, as well as some other minerals.